Relationship between body roundness index and obstructive sleep apnea: a population-based study - Gao, Haoyue; Zhang, Rundong; Wang, Peipei; Liu, Dai; Han, Jianxing; Wang, Bei (Frontiers in Nutrition, 2025)
ObjectivesThis study aimed to assess the relationship between body roundness index (BRI) and obstructive sleep apnea (OSA) risk and the difference in the ability of BRI and body mass index (BMI) to identify people at high risk for OSA in different conditions.MethodsThis study was based on the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2008 and 2015 to 2018. Participants were categorized into OSA high-risk and OSA low-risk groups via questionnaires about sleep. The potential relationship between BRI and high risk for OSA was explored using several statistical methods, including weighted logistic regression models, receiver operating characteristic curves (ROC), restricted cubic spline curves (RCS), interaction tests, and subgroup analyses.ResultsA total of 9,495 participants were included in this study, including 3,155 in the high-risk group and 6,340 in the low-risk group. In the crude model, BRI was positively associated with a high risk for OSA (OR = 1.23; 95% CI: 1.20–1.27). After adjusting for all covariates, higher BRI quartiles (Q4) were positively associated with high risk for OSA (OR = 3.22; 95% CI: 2.57–4.04). The RCS demonstrated that BRI was non-linearly associated with OSA risk. ROC analyses showed that BRI was better at identifying those at high risk for OSA in the normal-weight population than BMI. Subgroup analyses revealed stronger correlations in non-hypertensive and non-smoking populations.ConclusionsThere is a non-linear positive correlation between BRI and OSA risk, and early monitoring and managing BRI can help to identify people at high risk for OSA as early as possible and reduce the risk.